(untitled) (American Journal of Economics and Business Innovation, 2024)
Social media platforms are pivotal where consumers express opinions, seek information, and engage with brands. This study investigates the impact of social listening and social search on consumer behavior and brand engagement. Social listening involves tracking and analyzing online discussions across various platforms, while social search refers to utilizing social media platforms as search engines for information and product discovery. This research explores these practices to assess their influence on consumer perceptions, decision-making processes, purchasing behaviors, and brand loyalty. It employs a quantitative approach, utilizing regression, correlation analyses, and survey data from social media platforms. Key findings indicate that social listening and social search significantly affect consumer perceptions, aiding in product discovery and understanding brand attributes. Positive social media interactions strongly influence purchasing decisions, while active engagement with brands on social media is evident, especially when brands respond to interactions or run interactive campaigns. Moreover, social media emerges as a primary source of product information, with user-generated content deemed more authentic than traditional advertising. The study underscores the effectiveness of social listening tools in providing valuable insights for businesses, enhancing brand perception, and earning consumer loyalty. Gender is a significant factor influencing various aspects of consumer behavior on social media, while educational background has a comparatively more minor impact. Overall, this research illuminates the pivotal role of social listening, social search, and social media interactions on consumer behavior and fostering brand engagement. The findings offer actionable insights for businesses to tailor marketing strategies, prioritize engagement, and leverage user-generated content in the digital landscape.